Mircrobacia do Córrego da Gameleira em Ceres(GO) : degradação provocada pelo avanço do cultivo de cana-de-açúcar - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Starting from the deregulation of the Government in the 1990, sugarcane production has increased in area expansion in the state of Goiás. With deregulation, the agribusiness has started to have administrative independence, setting its prices according to costs. Also, the fiscal and financial incentives by the Federal Government and the Government of the state of Goiás have attracted traditional sugar-energy companies to the state and to the Ceres micro-region, where is located the Córrego da Gameleira microbasin, which receives in its area the crop of sugarcane. In the watershed of Gameleira Stream, located in the municipality of Ceres (GO), in the central portion of Goiás, sugar cane cultivation has the potential to cause soil degradation with erosion, mainly of the laminar type. Due to the declivity of the watershed relief, laminar erosion has the potential to remove organic matter from the soil surface, leaving nutrients at a disadvantage. With the transportation of nutrients, there is also the potential to transport chemical residues used in sugarcane cultivation processes, depositing them in the stream bed of the Gameleira Stream. In this way, it is necessary that there be conservationist interventions that soften the degradation processes to protect the soil from laminar erosion and the stream of chemical pollution, indicating the use of no-till and crop rotation. Keywords: sugarcane; deregulation of 1990; microbasin degradation; con
Keywords: cana-de-açúcar; Cana-de-açúcar - Desregulamentação de 1990; Degradação em microbacia; Degradação em microbacia - Práticas conservacionistas; sugarcane; sugarcane - deregulation of 1990; microbasin degradation; Microbasin degradation - Conservation practices; ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; GEOGRAFIA HUMANA::GEOGRAFIA ECONOMICA